The collapse of mangrove litterfall production following a climate-related forest loss in Brazil. (January 2021) - Gomes, Luiz Eduardo de Oliveira; Vescovi, Lucas Carneiro; Bernardino, Angelo Fraga
Abstract: Drought periods may change mangrove litterfall production through water deprivation and increasing tree evapotranspiration, but these impacts have been rarely estimated. In Brazil, an intense drought and strong winds impacted mangrove forests leading to mass tree mortality in 2016, suggesting that forest productivity also declined rapidly. Fifteen months after the initial impact, we started to monitor and quantify litterfall production in paired transects from disturbed and undisturbed mangroves. The litterfall production of the undisturbed forests (575 ± 28 Kg C ha −1 y −1 ) was 31- to 3-fold higher than that at the disturbed mangrove forests (18 to 169 Kg C ha −1 y −1 ). The strong decline in litterfall production may have implications to the export of nutrients to estuarine ecosystems. Our baseline suggests that mangrove forests are greatly vulnerable to climate impacts and that the litterfall production collapse in dead mangrove forests may impair marine ecosystem food webs. Graphical abstract: Unlabelled Image Highlights: Climate change can impact mangrove litterfall production in tropical estuaries SE Brazil Rhizophora mangle litterfall production is over 575 Kg C ha −1 y −1 Mangrove mortality decreased litterfall production by over 31-fold Lower mangrove production may decrease exports of carbon to estuaries